2022
DOI: 10.4314/met.v32i1.15
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary butterfly checklist (Lepidoptera: Papilionoidea) for Cyamudongo tropical forest fragment, Rwanda

Abstract: This study provides a preliminary checklist of butterfly species occurring in the Cyamudongo tropical forest fragment, Rwanda. A survey of butterflies was conducted seasonally from October 2019 to August 2020. Butterflies were collected for identification using butterfly nets and fruit-baited traps along trails within Cyamudongo forest. One hundred and sixty-two butterfly species were recorded in the Cyamudongo forest, including thirteen species that are endemic to the Albertine Rift. This preliminary checklis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Only a few studies focused on species level, namely Odonata (Uyizeye et al ., 2021), Lepidoptera (Uwizelimana et al ., 2022b, 2022a) and ants [Hymenoptera: Formicidae] (Nsengimana et al ., 2018; Nsengimana & Dekoninck, 2021; Nsengimana et al ., 2021; Nsengimana et al ., 2023). A recent study on ants has indicated that 105 ant species are known so far from Rwanda and highlighted that this number is an underestimation because Rwanda is in a biodiversity hotspot region for many other taxonomical groups too (Nsengimana et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies focused on species level, namely Odonata (Uyizeye et al ., 2021), Lepidoptera (Uwizelimana et al ., 2022b, 2022a) and ants [Hymenoptera: Formicidae] (Nsengimana et al ., 2018; Nsengimana & Dekoninck, 2021; Nsengimana et al ., 2021; Nsengimana et al ., 2023). A recent study on ants has indicated that 105 ant species are known so far from Rwanda and highlighted that this number is an underestimation because Rwanda is in a biodiversity hotspot region for many other taxonomical groups too (Nsengimana et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%